South Africa : Financial Sector Assessment Program-Detailed Assessment of Compliance on the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Detailed Assessment of Compliance on the Basel Core Principles for Effective Banking Supervision in South Africa. The South African banking system is highly concentrated with more than 90 percent of banking assets being controlled by the five largest banks. A suitable legal framework for banking supervision is in place to provide each responsible authority with the necessary legal powers to authorize banks, conduct ongoing supervision, address compliance with laws, and undertake timely corrective actions to address safety and soundness concerns. The responsibilities and objectives of each of the authorities involved in banking supervision are clearly defined in legislation and publicly disclosed.